Titanium silicalite molecular sieve as well as preparation method and application thereof
By optimizing the preparation method of titanium silicon molecular sieve, ensuring its 1H MAS NMR spectrum characteristics, the problem of long induction period of catalytic oxidation reaction of existing titanium silicon molecular sieve is solved, and more efficient catalytic performance and shorter induction period are achieved.
Patent Information
- Application Number
- CN202311416467.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
When existing titanium silicon molecular sieves interact with hydrogen peroxide, the induction period of catalytic oxidation reaction is long, resulting in a long time for the formation of the catalyst active center, which affects the reaction efficiency.
By adjusting the preparation method of titanium silicon molecular sieve, the signal peak intensity ratios at 1.96±0.15ppm and 1.68±0.15ppm in its 1H MAS NMR spectrum are above 0.95, and the generation and distribution of titanium active centers are optimized.
It effectively shortens the induction period of the catalyst, improves the catalytic performance, enhances the reaction activity, and reduces the preparation cost and difficulty.
Smart Images

Figure CN119898781A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of molecular sieves, and in particular, to a titanium silicon molecular sieve and a preparation method and application thereof. Background Art
[0002] Molecular sieves have high activity and product selectivity in many reactions due to their unique pore structure and active centers. Inserting titanium into the molecular sieve framework has opened up a new way to activate hydrogen peroxide and catalyze the conversion of organic matter under mild conditions. Among them, the discovery of TS-1 molecular sieve has laid the foundation for the development of new technologies for many oxidation reactions involving hydrogen peroxide, such as propylene epoxidation, cyclohexanone ammoximation, phenol hydroxylation, and thioether oxidation.
[0003] According to the different distribution of titanium atoms in TS-1, titanium species can be divided into four-coordinated titanium species, five / six-coordinated titanium species, anatase TiO2 and amorphous titanium species. Among them, four-coordinated framework titanium species have become the most studied and most widely recognized active species due to their good catalytic oxidation performance, while anatase TiO2 and amorphous titanium species cause H2O2 to self-decompose, which is not conducive to the catalytic oxidation reaction of TS-1 (Chemical Engineering Journal 253 (2014) 464–471).
[0004] Nevertheless, when the titanium silicon molecular sieve plays a catalytic oxidation role with hydrogen peroxide, the tetracoordinate framework titanium needs to hydrolyze at least one Si-O-Ti to produce Ti-OH, and further generate titanium peroxide species T-OOH. The peroxide species of titanium is the active center that reacts with organic molecules to produce oxygen-containing compounds. The active center titanium species of conventional titanium silicon molecular sieve is mainly tetracoordinate titanium, so in the actual reaction process, the catalyst produces an effective active center (titanium peroxide species) and plays a catalytic role, which requires a certain amount of time, ranging from a few hours to several days. This stage can be considered as the induction period of the catalyst. After the induction period ends, the catalyst performance reaches a normal level. In the induction period stage, the raw material conversion rate and target product selectivity of the catalyst are lower than the normal level, resulting in partial raw material waste and increasing the difficulty of operation. Chinese patent CN101850985A proposes a method for shortening the induction period of the titanium silicon molecular sieve obtained by crystallization after pore-forming agent expansion in phenol hydroxylation and cyclohexanone ammoxidation reaction. However, the preparation process of this method is long, which increases the difficulty and cost of preparing titanium silicon molecular sieve. Summary of the invention
[0005] The purpose of the present disclosure is to provide a titanium silicate molecular sieve and a preparation method and application thereof, which can effectively improve the activity of the titanium silicate molecular sieve catalyst, shorten the induction period of the catalyst, and have good catalytic performance.
[0006] In order to achieve the above-mentioned object, the present disclosure provides a titanium silicon molecular sieve in the first aspect. 1 In the HMAS NMR spectrum, there are signal peaks at 1.96±0.15ppm and 1.68±0.15ppm. The titanium silicalite molecular sieve has the following characteristics: 1 H MAS NMR characteristics:
[0007] The titanium silicalite molecular sieve 1 The peak intensity of the signal peak at 1.96±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.96 , the titanium silicalite 1 The peak intensity of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.68 , the titanium silicalite molecular sieve I 1.96 / I 1.68 The value of is 0.95 or more.
[0008] Optionally, the titanium silicalite molecular sieve has 1.96 / I 1.68 The value of is any value in the range of 1 to 1.5; preferably any value in the range of 1.1 to 1.3.
[0009] Optionally, the molar ratio of silicon element to titanium element in the titanium silicalite is preferably 1:(0.001-0.1), preferably 1:(0.01-0.04), and further preferably 1:(0.015-0.03).
[0010] Optionally, the average particle size of the titanium silicate molecular sieve is 20 to 1000 nm, preferably 100 to 500 nm; the BET specific surface area is 350 to 500 m 2 / g, preferably 400 to 470 m 2 / g; total pore volume is 0.15~0.6cm 3 / g, preferably 0.2 to 0.4 cm 3 / g;
[0011] Optionally, the configuration of the titanium silicalite molecular sieve is selected from one or more of MFI, MEL, BEA, MWW, and SVR; preferably, the configuration of the titanium silicalite molecular sieve is MFI.
[0012] A second aspect of the present disclosure provides a method for preparing a titanium silicon molecular sieve, comprising the following steps:
[0013] S1, mixing a silicon source, a template and water, and performing a first hydrothermal treatment to obtain a first sol;
[0014] S2, mixing the titanium source, the auxiliary agent and water, and performing a second hydrothermal treatment to obtain a second sol, wherein the auxiliary agent is selected from one or more of aldehyde compounds and condensates thereof;
[0015] S3, mixing the first sol and the second sol, and performing a third hydrothermal treatment to obtain a product slurry;
[0016] S4, subjecting the product slurry to solid-liquid separation, and subjecting the solid product obtained by the solid-liquid separation to roasting.
[0017] Optionally, in step S1, the molar ratio of silicon source: template: water is 1: (0.05-0.30): (10-40), preferably 1: (0.10-0.25): (15-30), and more preferably 1: (0.15-0.20): (18-25), wherein the silicon source is calculated as SiO2;
[0018] Preferably, in step S2, the molar ratio of titanium source: auxiliary agent: water is 1: (0.05-0.8): (5-20), preferably 1: (0.1-0.5): (7-17), and further preferably 1: (0.15-0.4): (9-15), wherein the titanium source is calculated as TiO2 and the auxiliary agent is calculated as CH2O; optionally, the molar ratio of silicon source in step S1: titanium source in step S2 is 1: (0.001-0.10), preferably 1: (0.01-0.04), and further preferably 1: (0.015-0.03).
[0019] Optionally, in step S1, the template is selected from one or more compounds having a structure represented by the following formula (M-1):
[0020] wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms;
[0021] Preferably, in formula (M-1), R1, R2, R3 and R4 are each independently selected from an alkyl or alkenyl group having 3 carbon atoms;
[0022] Further preferably, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide;
[0023] Optionally, the silicon source is selected from at least one of organic silicon esters, solid silica gel, white carbon black and silica sol; preferably at least one of organic silicon esters;
[0024] Optionally, the organic silicon ester is selected from one or more compounds having a structure represented by the following formula (M-2):
[0025]
[0026] Among them, R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate.
[0027] Optionally, in step S2, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;
[0028] Preferably, the organic titanium source is a titanium-containing organic acid ester, and the titanium-containing organic acid ester is selected from one or more compounds having a structure represented by the following formula (M-3):
[0029]
[0030] Among them, R e , R f, R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;
[0031] Preferably, the inorganic titanium source is selected from one or more of titanium tetrachloride, titanium trichloride, titanyl sulfate, titanocene dichloride, fluorotitanic acid and ammonium fluorotitanate;
[0032] Further preferably, the titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate;
[0033] Optionally, the auxiliary agent is selected from one or more of formaldehyde and its condensate, acetaldehyde and its condensate; preferably, the polymerization degree of the aldehyde compound condensate is 2 to 5; preferably, the auxiliary agent is a formaldehyde condensate; more preferably, it is trioxymethylene and / or tetraoxymethylene.
[0034] Optionally, in step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 30°C to 100°C, and the hydrothermal time is 0.5h to 24h; preferably, the hydrothermal temperature is 40°C to 80°C, and the hydrothermal time is 3h to 8h;
[0035] Alternatively, the temperature is first increased to 0°C to 40°C at a first heating rate for hydrothermal treatment for 1h to 5h, and then the temperature is increased to 60°C to 100°C at a second heating rate for continued treatment for 2h to 23h; preferably, the temperature is first increased to 30°C to 40°C at a first heating rate for hydrothermal treatment for 2h to 34h, and then the temperature is increased to 60°C to 90°C at a second heating rate for continued treatment for 3h to 12h;
[0036] Preferably, the first heating rate and the second heating rate are each independently 0.05°C / min to 2°C / min, preferably 0.4°C / min to 1.2°C / min;
[0037] Optionally, in step S2, the conditions of the second hydrothermal treatment include: the hydrothermal temperature is 20°C to 60°C, and the hydrothermal time is 0.5h to 6h; preferably, the hydrothermal temperature is 30°C to 50°C, and the hydrothermal time is 1h to 4h;
[0038] Alternatively, the temperature is first increased to 20°C to 40°C at the third heating rate for hydrothermal treatment for 0.5h to 3h, and then the temperature is increased to 40°C to 60°C at the fourth heating rate for continued treatment for 1h to 3h; preferably, the temperature is first increased to 30°C to 40°C at the third heating rate for hydrothermal treatment for 1h to 2h, and then the temperature is increased to 40°C to 50°C at the fourth heating rate for continued treatment for 1h to 2h;
[0039] Preferably, the third heating rate and the fourth heating rate are each independently 0.5°C / min to 1.5°C / min, preferably 0.8°C / min to 1.2°C / min;
[0040] Optionally, in step S3, the conditions of the third hydrothermal treatment include: the hydrothermal temperature is 120°C to 200°C, and the hydrothermal time is 2h to 96h; preferably, the hydrothermal temperature is 150°C to 180°C, and the hydrothermal time is 6h to 72h;
[0041] Alternatively, the temperature is first increased to 120°C to 160°C for hydrothermal treatment at the fifth heating rate for 1h to 24h, and then the temperature is increased to 160°C to 180°C for continued treatment for 6h to 72h at the sixth heating rate; preferably, the temperature is first increased to 120°C to 140°C for hydrothermal treatment at the fifth heating rate for 1h to 12h, and then the temperature is increased to 165°C to 175°C for continued treatment for 12h to 48h at the sixth heating rate;
[0042] Preferably, the fifth heating rate and the sixth heating rate are each independently 0.1° C. / min to 3° C. / min, preferably 0.5° C. / min to 1.5° C. / min.
[0043] Optionally, in step S4, the conditions of the calcination treatment include: a calcination temperature of 350°C to 650°C, and a calcination time of 2h to 10h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 4h to 8h;
[0044] Optionally, the method further comprises: washing and drying the solid product obtained by the solid-liquid separation treatment and then calcining it.
[0045] A third aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the second aspect of the present disclosure.
[0046] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the first aspect or the third aspect of the present disclosure in catalyzing organic reactions.
[0047] Optionally, the catalytic organic matter reaction includes a reaction of preparing propylene oxide by epoxidation of propylene; optionally, the reaction includes the following steps:
[0048] Under epoxidation reaction conditions, propylene, hydrogen peroxide, methanol and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;
[0049] Preferably, the epoxidation reaction conditions include: a molar ratio of propylene to hydrogen peroxide of 1.0 to 5.0:1, a molar ratio of methanol to hydrogen peroxide of 3 to 10:1, and a weight hourly space velocity of hydrogen peroxide of 0.01 h / min when a fixed bed is used as a reactor. -1 ~3h -1 ; The reaction temperature is 20℃~80℃.
[0050] Through the above technical solution, the present invention provides a titanium silicon molecular sieve and its preparation method and application. 1 In the H MAS NMR spectrum, there are signal peaks at 1.96±0.15ppm and 1.68±0.15ppm, and I 1.96 / I 1.68 The value is above 0.95, and the titanium silicon molecular sieve can have a more suitable titanium active center site, which can effectively improve the activity of the reaction and shorten the induction period of the catalytic reaction; at the same time, the preparation method of the titanium silicon molecular sieve provided by the present invention is simple, easy to implement and low in cost.
[0051] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0053] Figure 1 The titanium silicon molecular sieve TS-1 prepared in Comparative Example 2 1 H MAS NMR spectrum;
[0054] Figure 2 The titanium silicon molecular sieve HTS prepared in Comparative Example 3 1 H MAS NMR spectrum;
[0055] Figure 3 The titanium silicon molecular sieve TS-1-A prepared in Example 1 1 H MAS NMR spectrum;
[0056] Figure 4 The titanium silicon molecular sieve TS-1-E prepared in Example 51 H MAS NMR spectrum;
[0057] Figure 5 This is the XRD spectrum of the titanium silicon molecular sieve TS-1-A prepared in Example 1. DETAILED DESCRIPTION
[0058] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0059] The first aspect of the present disclosure provides a titanium silicon molecular sieve. 1 In the H MAS NMR spectrum, there are signal peaks at 1.96±0.15ppm and 1.68±0.15ppm. The titanium silicalite molecular sieve has the following characteristics: 1 H MAS NMR characteristics:
[0060] The titanium silicalite molecular sieve 1 The peak intensity of the signal peak at 1.96±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.96 , the titanium silicalite 1 The peak intensity of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.68 , the titanium silicalite molecular sieve I 1.96 / I 1.68 The value of is 0.95 or more.
[0061] The present invention discloses a titanium silicon molecular sieve. 1 In the H MAS NMR spectrum, there are signal peaks at 1.96±0.15ppm and 1.68±0.15ppm, and I 1.96 / I 1.68 The value is above 0.95, and the titanium silicon molecular sieve can have a more suitable titanium active center site, which can effectively improve the activity of the reaction and shorten the induction period of the catalytic reaction; at the same time, the preparation method of the titanium silicon molecular sieve provided by the present invention is simple, easy to implement and low in cost.
[0062] According to the present disclosure, the titanium silicon molecular sieve 1 The resonance absorption peak at 1.68±0.15ppm in the H MAS NMR spectrum is taken as the Si-OH signal peak, and the resonance absorption peak at 1.96±0.15ppm is taken as the resonance signal peak of hydrogen bonding between Si-OH and Ti-OH. 1 In the H MAS NMR spectrum, I 1.96 / I 1.68The value is higher than that of conventional titanium silicate molecular sieve (the I 1.96 / I 1.68 The value of is about 0.50 to 0.85), indicating that the titanium silicon molecular sieve disclosed in the present invention has more Ti-OH, and the Ti-OH and Si-OH have hydrogen bond interactions, which is more conducive to improving the activity of the catalytic reaction and shortening the induction period of the catalytic reaction. In the present disclosure, the "resonance signal peak" mentioned above refers to the presence of a point in the spectrum within the chemical shift range where the first-order derivative is equal to zero and the second-order derivative is less than zero.
[0063] In a preferred embodiment, the titanium silicalite molecular sieve has 1.96 / I 1.68 The value of is any value in the range of 1 to 1.5; preferably any value in the range of 1.1 to 1.3. The titanium silicon molecular sieve provided in this embodiment has more suitable titanium active center sites and more excellent catalytic performance.
[0064] In one embodiment, the molar ratio of silicon element to titanium element in the titanium silicalite is preferably 1:(0.001-0.1), preferably 1:(0.01-0.04), and more preferably 1:(0.015-0.03).
[0065] The titanium silicon molecular sieve provided by the present disclosure may or may not contain a mesoporous structure, its low-temperature nitrogen adsorption-desorption curve may or may not have a hysteresis loop, and its TEM image may or may not have an intracrystalline hollow structure.
[0066] In a specific embodiment, the average particle size of the titanium silicate molecular sieve is 20 to 1000 nm, preferably 100 to 500 nm; the BET specific surface area is 350 to 500 m 2 / g, preferably 400 to 470 m 2 / g; total pore volume is 0.15~0.6cm 3 / g, preferably 0.2 to 0.4 cm 3 / g.
[0067] In a specific embodiment, the configuration of the titanium silicalite molecular sieve is selected from one or more of MFI, MEL, BEA, MWW, and SVR; preferably, the configuration of the titanium silicalite molecular sieve is MFI;
[0068] Preferably, the titanium silicalite molecular sieve has a relative crystallinity of 40% or more, preferably 50% or more, more preferably 60% or more, further preferably 80% or more, and most preferably 85% or more, compared with an all-silicon molecular sieve of corresponding structure.
[0069] In the present disclosure, the titanium silicon molecular sieve provided by the present disclosure can be used as a catalytic active component, and its unique skeleton elements can be used, or it can be used as a carrier to further load active centers, or it can be prepared into a catalyst by mechanical mixing, kneading, tableting, extrusion, spraying, rolling ball, oil column, etc. with other catalysts, co-catalysts, structural additives, electronic additives, binders, inert carriers, etc. The reagents and preparation processes used can all be conventional reagents or processes in the art.
[0070] A second aspect of the present disclosure provides a method for preparing a titanium silicon molecular sieve, comprising the following steps:
[0071] S1, mixing a silicon source, a template and water, and performing a first hydrothermal treatment to obtain a first sol;
[0072] S2, mixing the titanium source, the auxiliary agent and water, and performing a second hydrothermal treatment to obtain a second sol, wherein the auxiliary agent is selected from one or more of aldehyde compounds and condensates thereof;
[0073] S3, mixing the first sol and the second sol, and performing a third hydrothermal treatment to obtain a product slurry;
[0074] S4, subjecting the product slurry to solid-liquid separation, and subjecting the solid product obtained by the solid-liquid separation to roasting.
[0075] The method for preparing titanium silicon molecular sieve provided by the present invention is simple in process, easy to implement and low in cost. The synthesis of titanium silicon molecular sieve is assisted by introducing an auxiliary agent containing aldehyde compounds and their condensates, which helps to improve the state of titanium element when entering the molecular sieve framework through the coordination of multiple carbonyl groups with titanium species, and directly synthesizes titanium silicon molecular sieve rich in Si-OH and Ti-OH hydrogen bonds, which can effectively improve the catalytic performance of the prepared titanium silicon molecular sieve.
[0076] In one embodiment, in step S1, the molar ratio of silicon source: template: water is 1: (0.05-0.30): (10-40), preferably 1: (0.10-0.25): (15-30), and further preferably 1: (0.15-0.20): (18-25), wherein the silicon source is calculated as SiO2.
[0077] In one embodiment, in step S2, the molar ratio of titanium source: auxiliary agent: water is 1: (0.05-0.8): (5-20), preferably 1: (0.1-0.5): (7-17), and further preferably 1: (0.15-0.4): (9-15), wherein the titanium source is calculated as TiO2 and the auxiliary agent is calculated as CH2O; optionally, the molar ratio of silicon source in step S1: titanium source in step S2 is 1: (0.001-0.10), preferably 1: (0.01-0.04), and further preferably 1: (0.015-0.03).
[0078] The catalytic performance of the titanium silicalite can be further improved by preparing the titanium silicalite according to the optimized molar ratio in the above embodiment.
[0079] In one embodiment, in step S1, the template is selected from one or more compounds having a structure represented by the following formula (M-1):
[0080] wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms;
[0081] Preferably, in formula (M-1), R1, R2, R3 and R4 are each independently selected from an alkyl or alkenyl group having 3 carbon atoms;
[0082] Further preferably, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably, it is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide.
[0083] In one embodiment, the silicon source is selected from at least one of organosilicon esters, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organosilicon esters; preferably, the SiO2 content in the solid silicon source (solid silica gel, white carbon black and silica sol) is not less than 99.99% by weight based on dry weight, and the total mass content of Fe, Al and Na impurities is less than 10 ppm; for example, the SiO2 content is 99.99-100% by weight, usually greater than 99.99 and less than 100% by weight. The solid silicon source can be high-purity silica gel and / or white carbon black, preferably white carbon black; wherein the SiO2 content in the high-purity silica gel is preferably greater than or equal to 99.99% by weight, for example, greater than 99.99% by weight and less than 100% by weight, and the total mass content of Fe, Al and Na impurities is less than 10 ppm. Based on the dry weight of the white carbon black, the SiO2 content in the white carbon black is preferably 99.99 wt% or more, for example, 99.99 to 100 wt%, for example, greater than 99.99 wt% and less than 100 wt%, and the total mass content of Fe, Al and Na impurities in the white carbon black is less than 10 ppm in terms of atoms. The specific surface area of the white carbon black is between 20 and 1000 m 2 / g, preferably 50 to 400 m 2 / g.
[0084] In a preferred embodiment, the organic silicon ester is selected from one or more compounds having the structure shown in the following formula (M-2):
[0085]
[0086] Among them, R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate.
[0087] In one embodiment, in step S2, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source;
[0088] Preferably, the organic titanium source is a titanium-containing organic acid ester, and the titanium-containing organic acid ester is selected from one or more compounds having a structure represented by the following formula (M-3):
[0089]
[0090] Among them, R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl;
[0091] Preferably, the inorganic titanium source is selected from one or more of titanium tetrachloride, titanium trichloride, titanyl sulfate, titanocene dichloride, fluorotitanic acid and ammonium fluorotitanate;
[0092] Further preferably, the titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate.
[0093] In a preferred embodiment, the auxiliary agent is selected from one or more of formaldehyde and its condensate, acetaldehyde and its condensate; preferably, the polymerization degree of the aldehyde compound condensate is 2 to 5; preferably, the auxiliary agent is a formaldehyde condensate; more preferably, it is trioxymethylene and / or tetraoxymethylene.
[0094] All raw materials and reagents used in the present invention can be purchased through common commercial channels, or prepared by known methods.
[0095] In one embodiment, the first hydrothermal treatment, the second hydrothermal treatment, and the third hydrothermal treatment in the present disclosure may be performed at a fixed temperature or at a variable temperature, and may be heated in a stepwise manner or in stages.
[0096] In one embodiment, in step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 30°C to 100°C, and the hydrothermal time is 0.5h to 24h; preferably, the hydrothermal temperature is 40°C to 80°C, and the hydrothermal time is 3h to 8h; or, first, the temperature is increased to 0°C to 40°C for hydrothermal treatment for 1h to 5h at a first heating rate, and then the temperature is increased to 60°C to 100°C for continued treatment for 2h to 23h at a second heating rate; preferably, the temperature is increased to 30°C to 40°C for hydrothermal treatment for 2h to 34h at a first heating rate, and then the temperature is increased to 60°C to 90°C for continued treatment for 3h to 12h at a second heating rate; preferably, the first heating rate and the second heating rate are each independently 0.05°C / min to 2°C / min, preferably 0.4°C / min to 1.2°C / min; in the present disclosure, the first hydrothermal treatment is carried out under stirring, and can also be carried out under normal pressure, negative pressure, or pressurized conditions;
[0097] In step S2, the conditions of the second hydrothermal treatment include: the hydrothermal temperature is 20℃~60℃, and the hydrothermal time is 0.5h~6h; preferably, the hydrothermal temperature is 30℃~50℃, and the hydrothermal time is 1h~4h; or, firstly, the temperature is increased to 20℃~40℃ for hydrothermal treatment at the third heating rate for 0.5h~3h, and then the temperature is increased to 40℃~60℃ for continuous treatment at the fourth heating rate for 1h~3h; preferably, firstly, the temperature is increased to 30℃~40℃ for hydrothermal treatment at the third heating rate for 1h~2h, and then the temperature is increased to 40℃~50℃ for continuous treatment at the fourth heating rate for 1h~2h; the third heating rate and the fourth heating rate are each independently 0.5℃ / min~1.5℃ / min, preferably 0.8℃ / min~1.2℃ / min; in the present disclosure, the second hydrothermal treatment is carried out under stirring;
[0098] In step S3, the conditions of the third hydrothermal treatment include: the hydrothermal temperature is 120℃~200℃, and the hydrothermal time is 2h~96h; preferably, the hydrothermal temperature is 150℃~180℃, and the hydrothermal time is 6h~72h; or, first heat the temperature to 120℃~160℃ at the fifth heating rate for hydrothermal treatment for 1h~24h, and then heat the temperature to 160℃~180℃ at the sixth heating rate for continuous treatment for 6h~72h; preferably, first heat the temperature to 120℃~140℃ at the fifth heating rate for hydrothermal treatment for 1h~12h, and then heat the temperature to 165℃~175℃ at the sixth heating rate for continuous treatment for 12h~48h; preferably, the fifth heating rate and the sixth heating rate are each independently 0.1℃ / min~3℃ / min, preferably 0.5℃ / min~1.5℃ / min.
[0099] In one embodiment, in step S4, the conditions of the calcination treatment include: a calcination temperature of 350°C to 650°C, and a calcination time of 2h to 10h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 4h to 8h;
[0100] Optionally, the method further comprises: washing and drying the solid product obtained from the solid-liquid separation treatment and then calcining it. In the present disclosure, the solid-liquid separation treatment can be a method such as sedimentation, centrifugation, filtration, evaporation, etc.; the washing treatment can be washing the molecular sieve with water or an organic solvent to achieve a pH value of the washing liquid of less than 9; the drying treatment can remove most of the water in the molecular sieve to reduce the amount of water evaporation during calcination, and the temperature of the drying treatment can be 100°C to 200°C; the calcination treatment can remove the template in the molecular sieve to obtain a titanium silicon molecular sieve without the template.
[0101] A third aspect of the present disclosure provides a titanium silicon molecular sieve prepared according to the method described in the second aspect of the present disclosure.
[0102] The fourth aspect of the present disclosure provides the use of the titanium silicon molecular sieve described in the first aspect or the third aspect of the present disclosure in catalyzing organic reactions.
[0103] In the present disclosure, the organic matter reactions include: catalytic oxidation reaction (olefin oxidation / epoxidation to prepare aldehydes, ketones, acids, epoxy compounds, and vicinal diols; alkane oxidation to prepare alcohols, aldehydes, and acids; alcohol oxidation to prepare ketones and acids; aldehyde oxidation to prepare acids; aromatic hydrocarbon oxidation to prepare phenols; sulfide oxidation to prepare sulfoxides and sulfones), reduction reaction, oximation reaction (aldehyde / ketone ammoximation to prepare amides and lactams), aldol condensation reaction, substitution / halogenation reaction, elimination reaction, ester exchange reaction, dehydration reaction, etherification reaction, esterification reaction, double bond / triple bond addition reaction, diene addition reaction, Beckmann rearrangement reaction (cyclohexanone oxime gas phase rearrangement to prepare caprolactam), hydrogen transfer reaction, etc.
[0104] In a preferred embodiment, the catalytic organic reaction includes a reaction of preparing propylene oxide by epoxidation of propylene; optionally, the reaction includes the following steps:
[0105] Under epoxidation reaction conditions, propylene, hydrogen peroxide, methanol and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve;
[0106] Preferably, the epoxidation reaction conditions include: a molar ratio of propylene to hydrogen peroxide of 1.0 to 5.0:1, a molar ratio of methanol to hydrogen peroxide of 3 to 10:1, and a weight hourly space velocity of hydrogen peroxide of 0.01 h / min when a fixed bed is used as a reactor. -1 ~3h -1 ; The reaction temperature is 20℃~80℃.
[0107] In the application of the titanium silicalite provided in the present disclosure, the titanium silicalite or the catalyst containing the titanium silicalite can be used in the form of powder or shaped spheres, strips, cakes, granules, etc., and can be mixed with other catalysts; the application can be carried out in a variety of reactors such as kettle reactors, slurry bed reactors, fixed bed reactors, fluidized bed reactors, moving bed reactors, microchannel reactors, etc.; the reaction raw materials and catalysts can be fed all at once, intermittently, or continuously.
[0108] It will be understood by those skilled in the art that the separation of the product and the catalyst can be achieved in a variety of ways. For example, when the original powdered molecular sieve is used as the catalyst, the product separation and the catalyst recovery and reuse can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation, etc. Alternatively, the catalyst can be formed and loaded into a fixed bed reactor, and the catalyst can be recovered after the reaction is completed. The separation and recovery methods of various catalysts can be known methods.
[0109] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.
[0110] In the following embodiments and comparative examples:
[0111] The structure of the molecular sieve was determined by XRD analysis, and the test instrument was Siemens D5005 X-ray diffractometer; the test method included: Cu target, Kα radiation, Ni filter, tube point voltage 40kV, tube current 250mA, scintillation counter, step width 0.02°. Scanning range 2θ = 5° to 35°, scanning rate 0.4 (°) / min.
[0112] The chemical composition of the molecular sieve was analyzed and determined using a Rigaku 3721E fluorescence spectrometer.
[0113] 1 H MAS NMR was performed on a Bruker AVANCE 600 MHz NMR instrument with a rotor speed of 12 kHz, a cycle delay of 2 s, and 256 samples.
[0114] Unless otherwise specified, the raw materials used in the examples are all chemically pure reagents, which can be purchased through common commercial channels or prepared according to methods known in the art.
[0115] In the following examples and comparative examples, the relative crystallinity of the molecular sieves is based on the crystallinity of the all-silicon molecular sieve prepared in Comparative Example 1.
[0116] Comparative Example 1
[0117] In this comparative example, MFI type all-silicon molecular sieve S-1 was synthesized.
[0118] According to the molar ratio of silicon source (in terms of SiO2): template: water of 1:0.2:25, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 80°C for about 8 hours to obtain a sol. The obtained sol was treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was lower than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the S-1 product. S-1 was tested by XRD, and it had an MFI-type skeleton structure, and the relative crystallinity was recorded as 100%.
[0119] Comparative Example 2
[0120] In this comparative example, conventional MFI type titanium silicalite TS-1 was synthesized.
[0121] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.025:0.2:25, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 80°C for about 8 hours to obtain a sol. The obtained sol was treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1 product. TS-1 was subjected to XRD testing, which showed that it had an MFI-type skeleton structure with a relative crystallinity of 85%. The chemical composition of TS-1 was analyzed by XRF, and it was found that the molar ratio of silicon and titanium elements was 1:0.025. TS-1 was subjected to 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0122] Comparative Example 3
[0123] In this comparative example, conventional MFI type titanium silicalite HTS is synthesized (refer to the method of Chinese patent CN1260241A).
[0124] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.025:0.2:25, tetraethyl silicate, tetrabutyl titanate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, stirred at 30°C for about 2 hours, and then stirred at 80°C for about 8 hours to obtain a sol. The obtained sol was treated at 170°C for 72 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was lower than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the intermediate TS-1 product. TS-1 was then mixed with tetrapropylammonium hydroxide and water in a weight ratio of 1:0.4:5, and then treated at 170°C for 24 hours. The obtained slurry was filtered, dried, and calcined according to the above method to obtain the product HTS. HTS was tested by XRD, which had an MFI-type skeleton structure and a relative crystallinity of 95%. XRF analysis of the chemical composition of HTS revealed that the molar ratio of silicon to titanium was 1:0.025. 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0125] Example 1
[0126] In this example, MFI type titanium silicalite TS-1-A was synthesized.
[0127] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.025:0.2:25, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 30°C at 0.5°C / min, stirred at 30°C for about 2 hours, then heated to 80°C at 0.5°C / min, stirred at 80°C for about 8 hours to obtain the first sol. According to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.5:16, tetrabutyl titanate, tetraoxymethylene and water were mixed, treated at 40°C for 2 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 170°C for 72 hours, then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was lower than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain TS-1-A product. XRD test of TS-1-A was performed, as shown in FIG. Figure 5 As shown in the figure, there is a peak at 2θ of 22° to 25°, indicating that it has an MFI-type skeleton structure and a relative crystallinity of 88%. XRF analysis of the chemical composition of TS-1-A revealed that its silicon-titanium molar ratio was 1:0.025. 1H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0128] Comparative Example 4
[0129] This comparative example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0130] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): template agent: water of 1:0.025:0.0125:0.2:25, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed with tetrabutyl titanate, tetraformaldehyde and water, stirred at 30°C for about 2 hours, then stirred at 80°C for about 8 hours, and then placed in a hydrothermal reactor for treatment at 170°C for 72 hours. The obtained slurry was then filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the D-1 product. XRD test of D-1 showed a relative crystallinity of 86%. XRF analysis of the chemical composition of D-1 showed that its silicon-titanium molar ratio was 1:0.025. 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0131] Example 2
[0132] In this example, MFI type titanium silicalite TS-1-B is synthesized.
[0133] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.015:0.2:18, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 30°C at 0.5°C / min, stirred at 30°C for about 2 hours, then heated to 80°C at 0.8°C / min, stirred at 80°C for about 8 hours to obtain the first sol. According to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.1:8, tetrabutyl titanate, tetraoxymethylene and water were mixed, treated at 50°C for 3 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 170°C for 72 hours. The obtained slurry was then filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1-B product. TS-1-B was subjected to XRD testing, and it had an MFI-type skeleton structure with a relative crystallinity of 86%. The chemical composition of TS-1-B was analyzed by XRF, and it was found that the molar ratio of silicon to titanium was 1:0.015. 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0134] Example 3
[0135] In this example, MFI type titanium silicalite molecular sieve TS-1-C is synthesized.
[0136] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.025:0.2:25, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 40°C at 1°C / min, stirred at 40°C for about 2 hours, then heated to 90°C at 0.8°C / min, stirred at 90°C for about 3 hours to obtain the first sol. According to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.25:12, tetrabutyl titanate, tetraoxymethylene and water were mixed, treated at 50°C for 3 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 170°C for 12 hours. The obtained slurry was then filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1-C product. TS-1-C was subjected to XRD testing, and it had an MFI-type skeleton structure with a relative crystallinity of 88%. The chemical composition of TS-1-C was analyzed by XRF, and it was found that the molar ratio of silicon to titanium was 1:0.025.1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0137] Example 4
[0138] In this example, MFI type titanium silicalite TS-1-D was synthesized.
[0139] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.02:0.18:20, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 30°C at 0.8°C / min, stirred at 30°C for about 2 hours, then heated to 80°C at 1°C / min, stirred at 80°C for about 6 hours to obtain the first sol. According to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.25:12, tetraethyl titanate, trioxymethylene and water were mixed, treated at 40°C for 2 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 170°C for 12 hours. The obtained slurry was then filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1-D product. TS-1-D was subjected to XRD testing, and it had an MFI-type skeleton structure with a relative crystallinity of 86%. The chemical composition of TS-1-D was analyzed by XRF, and it was found that the molar ratio of silicon to titanium was 1:0.02. 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0140] Example 5
[0141] In this example, MFI type titanium silicalite TS-1-E is synthesized.
[0142] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template agent: water of 1:0.015:0.15:20, tetraethyl silicate, propylene tripropyl ammonium hydroxide (25 wt%) solution and deionized water were mixed, the temperature was raised to 30°C at 0.6°C / min, stirred at 30°C for about 2 hours, then the temperature was raised to 80°C at 0.6°C / min, and stirred at 80°C for about 6 hours to obtain the first sol. According to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.3:12, tetraethyl titanate, trioxymethylene and water were mixed, treated at 40°C for 2 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 170°C for 72 hours. The obtained slurry was then filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1-E product. TS-1-E was subjected to XRD testing, and it had an MFI-type skeleton structure with a relative crystallinity of 90%. The chemical composition of TS-1-E was analyzed by XRF, and it was found that the molar ratio of silicon to titanium was 1:0.015. 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0143] Example 6
[0144] In this example, MFI type titanium silicalite TS-1-F is synthesized.
[0145] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template agent: water of 1:0.02:0.15:25, tetraethyl silicate, allyl tripropyl ammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 40°C at 0.6°C / min, stirred at 40°C for about 3 hours, then heated to 90°C at 1°C / min, stirred at 90°C for about 8 hours to obtain the first sol. According to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.25:10, tetraethyl titanate, trioxymethylene and water were mixed, treated at 40°C for 2 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 170°C for 12 hours. The obtained slurry was then filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours to obtain the TS-1-F product. TS-1-F was subjected to XRD testing, and it had an MFI-type skeleton structure with a relative crystallinity of 91%. The chemical composition of TS-1-F was analyzed by XRF, and it was found that the molar ratio of silicon to titanium was 1:0.02.1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0146] Example 7
[0147] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0148] According to the molar ratio of silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water of 1:0.05:0.3:40, tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, and according to the molar ratio of titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water of 1:0.8:20, tetrabutyl titanate, tetraformaldehyde and water were mixed; the rest of the process was the same as in Example 1 to obtain the TS-1-G product. TS-1-G was subjected to XRD testing, and it was found that it had an MFI-type skeleton structure with a relative crystallinity of 86%. The chemical composition of TS-1-G was analyzed by XRF, and it was found that the molar ratio of silicon and titanium elements was 1:0.05. TS-1-G was subjected to 1 HMAS NMR test found that it has resonance absorption peaks near 1.96ppm and 1.68ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0149] Example 8
[0150] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the auxiliary agent tetraoxymethylene is replaced by formaldehyde, and the rest of the process is the same as Example 1 to obtain TS-1-H product, and I 1.96 / I 1.68 The values are listed in Table 1.
[0151] Example 9
[0152] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the auxiliary agent tetraoxymethylene is replaced by triacetaldehyde, and the rest of the process is the same as Example 1 to obtain TS-1-I product, and I 1.96 / I 1.68 The values are listed in Table 1.
[0153] Comparative Example 5
[0154] This comparative example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0155] Tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed in a molar ratio of 1:0.15:0.5:50 for silicon source (in terms of SiO2): titanium source (in terms of TiO2): template: water; tetrabutyl titanate, tetraformaldehyde and water were mixed in a molar ratio of 1:1:30 for titanium source (in terms of TiO2): auxiliary agent (in terms of CH2O): water; the rest of the process was the same as in Example 1 to obtain product D-2. XRD test was performed on D-2, which showed that it had an MFI-type skeleton structure with a relative crystallinity of 88%. XRF analysis of the chemical composition of D-2 showed that its molar ratio of silicon to titanium elements was 1:0.15. 1 H MAS NMR test revealed that it had resonance absorption peaks at around 1.96 ppm and 1.68 ppm. 1.96 / I 1.68 The values are listed in Table 1.
[0156] Example 10
[0157] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0158] Tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 30°C at 0.5°C / min, stirred at 30°C for about 2 hours, then heated to 80°C at 0.6°C / min, and stirred at 80°C for about 8 hours to obtain the first sol. Tetrabutyl titanate, tetraoxymethylene and water were mixed, heated to 40°C at 1°C / min, stirred for 1 hour, then heated to 60°C at 1°C / min, stirred for 2 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor, first heated to 130°C at 1°C / min, treated for 6 hours, then heated to 170°C at 1°C / min, treated for 24 hours; then the obtained slurry was filtered, washed with deionized water until the filtrate pH was lower than 9, dried at 120°C for 6 hours, and calcined at 550°C for 6 hours. The rest of the process was the same as in Example 1 to obtain TS-1-J product. 1.96 / I 1.68 The values are listed in Table 1.
[0159] Embodiment 11
[0160] This example refers to the preparation method in Example 1, and the difference from Example 1 is that:
[0161] Tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 25°C at 0.2°C / min, stirred at 25°C for about 1 hour, then heated to 100°C at 2°C / min, and stirred at 100°C for about 20 hours to obtain the first sol. Tetrabutyl titanate, trioxymethylene and water were mixed and treated at 60°C for 0.5 hour to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 120°C for 96 hours, after which the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 350°C for 10 hours. The remaining process was the same as in Example 1 to obtain the TS-1-K product. 1.96 / I 1.68 The values are listed in Table 1.
[0162] Comparative Example 12
[0163] Referring to the preparation method in Example 1, the difference from Example 1 is that:
[0164] Tetraethyl silicate, tetrapropylammonium hydroxide (25 wt%) solution and deionized water were mixed, heated to 60°C at 3°C / min, stirred at 60°C for about 0.2 hours, then heated to 120°C at 3°C / min, and stirred at 100°C for about 1 hour to obtain the first sol. Tetrabutyl titanate, trioxymethylene and water were mixed, treated at 100°C for 10 hours to obtain the second sol. The first sol and the second sol were mixed, placed in a hydrothermal reactor and treated at 260°C for 0.5 hours, and then the obtained slurry was filtered, washed with deionized water until the pH of the filtrate was less than 9, dried at 120°C for 6 hours, and calcined at 300°C for 1 hour. The rest of the process was the same as in Example 1 to obtain the TS-1-L product. 1.96 / I 1.68 The values are listed in Table 1.
[0165] The silicon-titanium molar ratio, I 1.96 / I 1.68 The relative crystallinity and other data are listed in Table 1 below.
[0166] Table 1
[0167]
[0168] Among them, taking the titanium silicon molecular sieve prepared in Example 1 as an example, the titanium silicon molecular sieve 1 The peak intensity I of the signal peak at 1.96±0.15 ppm in the H MAS NMR spectrum 1.96 The peak intensity of the signal peak at the position of 1.68±0.15ppm is 2790. 1.68It is 2625.
[0169] According to the data in Table 1 above, it can be seen that the titanium silicon molecular sieves prepared by the method provided in Examples 1 to 11 have an I 1.96 / I 1.68 The values are all above 0.95; while in Comparative Examples 2 to 3, titanium silicon molecular sieves TS-1 and HTS were synthesized by conventional methods, combined with Figure 1 and 2 It can be seen that the titanium silicon molecular sieves obtained in Comparative Examples 2 to 3 have only one spectral peak (at 1.68 ppm) which is relatively obvious, and the spectral peak at 1.96 ppm is relatively weak, and the peak at 1.96 ppm is relatively weak. 1.96 / I 1.68 The calculated value is less than 0.95 (only 0.76 to 0.81); Comparative Example 4 did not prepare the titanium silicon molecular sieve according to the method disclosed in the present invention (the first sol and the second sol were not prepared in steps), and Comparative Example 5 did not prepare the titanium silicon molecular sieve according to the raw material addition ratio specified in the present invention. The I of the titanium silicon molecular sieve prepared in Comparative Examples 4 to 5 is 1.96 / I 1.68 The values are 0.85 to 0.91, all below 0.95. From the above data comparison, it can be seen that the titanium silicon molecular sieves prepared by the method provided in Examples 1 to 11 using the present disclosure have more suitable titanium active center sites, which can effectively improve the activity of the reaction and shorten the induction period of the catalytic reaction.
[0170] Evaluation test case
[0171] This test example is used to evaluate the performance of the titanium silicon molecular sieve prepared in the embodiment, comparative example and comparative example as a catalyst in catalyzing the propylene epoxidation reaction. Specifically, it includes the following process:
[0172] Propylene epoxidation reaction was evaluated in a fixed bed reactor. The catalyst loading was 5 mL, and the feed was divided into two routes, a propylene route and a methanol-hydrogen peroxide mixture route. The two routes were transported to the inlet of the reaction tube by a feed pump for mixing, and then entered the catalyst bed for reaction. The raw materials were fed in from the bottom and discharged from the top. Among them, the molar ratio of propylene to hydrogen peroxide was 3:1, the molar ratio of methanol to hydrogen peroxide was 8:1, and the weight hourly space velocity of hydrogen peroxide was 0.9h -1 , the reaction temperature was controlled at 40°C. The reaction was timed from the time the raw materials entered the reactor, and samples were taken for analysis at regular intervals to obtain the product and determine the composition. The evaluation indicators are shown below, and the evaluation results are listed in Tables 2 and 3 below.
[0173] Hydrogen peroxide conversion rate (mol %) = (molar number of hydrogen peroxide in the raw material - molar number of hydrogen peroxide in the product) / molar number of hydrogen peroxide in the raw material × 100%;
[0174] Propylene oxide selectivity (mol %) = the number of moles of propylene oxide produced in the product / the number of moles of all products produced × 100%;
[0175] The conversion rate of hydrogen peroxide was measured by sodium thiosulfate titration, and the selectivity of propylene oxide was measured by gas chromatography, wherein the chromatographic analysis conditions were: Agilent-6890 chromatograph, HP-5 capillary column, injection volume 0.5 μL, injection port temperature 280°C. The column temperature was maintained at 100°C for 2 min, then increased to 250°C at a rate of 15°C / min and maintained for 10 min. FID detector, detector temperature 300°C.
[0176] Table 2
[0177]
[0178] Table 3
[0179]
[0180] It can be seen from the data in Tables 1 to 3 above that compared with titanium silicalite TS-1 and HTS synthesized by conventional methods in Comparative Examples 2 to 3, titanium silicalite D-1 to D-2 and I 1.96 / I 1.68 The titanium silicon molecular sieve TS-1-L of Comparative Example 12 has an I value of less than 0.95, and the titanium silicon molecular sieves TS-1-A to TS-1-F prepared according to the method provided in the present disclosure in Examples 1 to 11 have an I value of less than 0.95. 1.96 / I 1.68 The value is above 0.95, and in the early stage of the catalytic propylene epoxidation reaction, a higher hydrogen peroxide conversion rate and propylene oxide selectivity can be achieved at the same reaction time, and the highest hydrogen peroxide conversion rate and the highest propylene oxide selectivity can be achieved in a shorter time, indicating that the titanium silicalite provided by the present invention has a more suitable titanium active center site, which can effectively improve the activity of the reaction and effectively shorten the induction period of the catalytic reaction.
[0181] Comparing Examples 1 to 6 with Example 7, it can be seen that Examples 1 to 6 synthesize titanium silicon molecular sieves according to the preferred raw material addition ratio provided in the present disclosure. Compared with the titanium silicon molecular sieve TS-1-G prepared in Example 7, the titanium silicon molecular sieves TS-1-A to TS-1-F prepared in Examples 1 to 6 have an I 1.96 / I 1.68 The value of is in the range of 1 to 1.5. In the early stage of the catalytic propylene epoxidation reaction, a higher hydrogen peroxide conversion rate and propylene oxide selectivity can be achieved at the same reaction time, and the highest hydrogen peroxide conversion rate and the highest propylene oxide selectivity can be achieved in a shorter time.
[0182] Further, in Examples 1 to 6, Examples 3 to 6 prepared titanium silicon molecular sieves TS-1-C to TS-1-F I 1.96 / I 1.68 The value of is in the more preferred range of 1.1 to 1.3. Compared with the titanium silicalite molecular sieves in Examples 1 to 2 that are not within this range, the titanium silicalite molecular sieves TS-1-C to TS-1-F in Examples 3 to 6 can achieve higher hydrogen peroxide conversion and propylene oxide selectivity at the same reaction time in the early stage of the catalytic propylene epoxidation reaction, and can also achieve the highest hydrogen peroxide conversion and the highest propylene oxide selectivity in a shorter time.
[0183] Comparing Example 1 with Example 7, Example 1 prepared titanium silicon molecular sieve according to the preferred raw material molar ratio provided in the present disclosure; comparing Example 1 with Examples 8 to 9, Example 1 used tetraformaldehyde; comparing Example 1 with Example 11, it can be seen that Example 1 synthesized titanium silicon molecular sieve according to the preferred process; compared with the titanium silicon molecular sieves TS-1-G to TS-1-I and TS-1-K obtained in Examples 7 to 9 and 11, the titanium silicon molecular sieve TS-1-A has a higher I 1.96 / I 1.68 The value of indicates that TS-1-A has a more suitable titanium active center site and has better catalytic performance. For example, TS-1-A can have a higher hydrogen peroxide conversion rate at the same reaction time.
[0184] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0185] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0186] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A titanium silicon molecular sieve, characterized in that: The titanium silicate molecular sieve 1 In the H MAS NMR spectrum, there are signal peaks at 1.96±0.15ppm and 1.68±0.15ppm. The titanium silicalite molecular sieve has the following characteristics: 1 H MAS NMR characteristics: The titanium silicalite molecular sieve 1 The peak intensity of the signal peak at 1.96±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.96 , the titanium silicalite 1 The peak intensity of the signal peak at 1.68±0.15 ppm in the H MAS NMR spectrum is recorded as I 1.68 , the titanium silicalite molecular sieve I 1.96 / I 1.68 The value of is 0.95 or more.
2. The titanium silicon molecular sieve according to claim 1, characterized in that: The titanium silicalite molecular sieve 1.96 / I 1.68 The value of is any value in the range of 1 to 1.5; preferably any value in the range of 1.1 to 1.
3.
3. The titanium silicon molecular sieve according to claim 1, characterized in that: The molar ratio of silicon element to titanium element in the titanium silicalite molecular sieve is preferably 1:(0.001-0.1), preferably 1:(0.01-0.04), and more preferably 1:(0.015-0.03).
4. The titanium silicon molecular sieve according to claim 1, characterized in that: The average particle size of the titanium silicate molecular sieve is 20 to 1000 nm, preferably 100 to 500 nm; the BET specific surface area is 350 to 500 m 2 / g, preferably 400 to 470 m 2 / g; total pore volume is 0.15~0.6cm 3 / g, preferably 0.2 to 0.4 cm 3 / g; Optionally, the configuration of the titanium silicalite molecular sieve is selected from one or more of MFI, MEL, BEA, MWW, and SVR; preferably, the configuration of the titanium silicalite molecular sieve is MFI.
5. A method for preparing titanium silicon molecular sieve, characterized in that: The following steps are involved: S1, mixing a silicon source, a template and water, and performing a first hydrothermal treatment to obtain a first sol; S2, mixing the titanium source, the auxiliary agent and water, and performing a second hydrothermal treatment to obtain a second sol, wherein the auxiliary agent is selected from one or more of aldehyde compounds and condensates thereof; S3, mixing the first sol and the second sol, and performing a third hydrothermal treatment to obtain a product slurry; S4, subjecting the product slurry to solid-liquid separation, and subjecting the solid product obtained by the solid-liquid separation to roasting.
6. The method according to claim 5, characterized in that In step S1, the molar ratio of silicon source: template: water is 1: (0.05-0.30): (10-40), preferably 1: (0.10-0.25): (15-30), and more preferably 1: (0.15-0.20): (18-25), wherein the silicon source is calculated as SiO2; Preferably, in step S2, the molar ratio of titanium source: auxiliary agent: water is 1: (0.05-0.8): (5-20), preferably 1: (0.1-0.5): (7-17), and further preferably 1: (0.15-0.4): (9-15), wherein the titanium source is calculated as TiO2 and the auxiliary agent is calculated as CH2O; optionally, the molar ratio of silicon source in step S1: titanium source in step S2 is 1: (0.001-0.10), preferably 1: (0.01-0.04), and further preferably 1: (0.015-0.03).
7. The method according to claim 5, characterized in that In step S1, the template is selected from one or more compounds having a structure represented by the following formula (M-1): wherein R1, R2, R3 and R4 are each independently selected from an alkyl group having 2 to 4 carbon atoms and an alkenyl group having 2 to 4 carbon atoms; Preferably, in formula (M-1), R1, R2, R3 and R4 are each independently selected from an alkyl or alkenyl group having 3 carbon atoms; Further preferably, the first template is selected from one or more of tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, diallyldipropylammonium hydroxide, diallyldipropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, diallylpropenylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, diallylallylpropylammonium hydroxide, triallylpropylammonium hydroxide, triallylpropylammonium hydroxide, tetraallylammonium hydroxide and tetraallylammonium hydroxide; preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide, propenyltripropylammonium hydroxide, allylpropenyldipropylammonium hydroxide, triallylpropylammonium hydroxide and tetraallylammonium hydroxide; further preferably one or more selected from tetrapropylammonium hydroxide, allyltripropylammonium hydroxide and propenyltripropylammonium hydroxide; Optionally, the silicon source is selected from at least one of organic silicon esters, solid silica gel, white carbon black and silica sol; preferably at least one of organic silicon esters; Optionally, the organic silicon ester is selected from one or more compounds having a structure represented by the following formula (M-2): Among them, R a , R b , R c and R d Each is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, the R a , R b , R c and R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicate; further preferably, it is selected from one or more of tetramethyl silicate, tetraethyl silicate and dimethyl diethyl silicate.
8. The method according to claim 5, characterized in that In step S2, the titanium source is selected from one or more of an organic titanium source and an inorganic titanium source; Preferably, the organic titanium source is a titanium-containing organic acid ester, and the titanium-containing organic acid ester is selected from one or more compounds having a structure represented by the following formula (M-3): Among them, R e , R f , R g and R h are each selected from an alkyl group having 1 to 6 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms, and more preferably R e , R f , R g and R h are independently selected from a straight chain alkyl group having 2 to 4 carbon atoms and a branched chain alkyl group having 2 to 4 carbon atoms; optionally, R e , R f , R g and R h Each of the following groups is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl and isohexyl; preferably each of the following groups is independently selected from one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl; Preferably, the inorganic titanium source is selected from one or more of titanium tetrachloride, titanium trichloride, titanyl sulfate, titanocene dichloride, fluorotitanic acid and ammonium fluorotitanate; Further preferably, the titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate and tetrabutyl titanate; Optionally, the auxiliary agent is selected from one or more of formaldehyde and its condensate, acetaldehyde and its condensate; preferably, the polymerization degree of the aldehyde compound condensate is 2 to 5; preferably, the auxiliary agent is a formaldehyde condensate; more preferably, it is trioxymethylene and / or tetraoxymethylene.
9. The method according to claim 5, characterized in that In step S1, the conditions of the first hydrothermal treatment include: the hydrothermal temperature is 30°C to 100°C, and the hydrothermal time is 0.5h to 24h; preferably, the hydrothermal temperature is 40°C to 80°C, and the hydrothermal time is 3h to 8h; Alternatively, the temperature is first increased to 0°C to 40°C at a first heating rate for hydrothermal treatment for 1h to 5h, and then the temperature is increased to 60°C to 100°C at a second heating rate for continued treatment for 2h to 23h; preferably, the temperature is first increased to 30°C to 40°C at a first heating rate for hydrothermal treatment for 2h to 34h, and then the temperature is increased to 60°C to 90°C at a second heating rate for continued treatment for 3h to 12h; Preferably, the first heating rate and the second heating rate are each independently 0.05°C / min to 2°C / min, preferably 0.4°C / min to 1.2°C / min; Optionally, in step S2, the conditions of the second hydrothermal treatment include: the hydrothermal temperature is 20°C to 60°C, and the hydrothermal time is 0.5h to 6h; preferably, the hydrothermal temperature is 30°C to 50°C, and the hydrothermal time is 1h to 4h; Alternatively, the temperature is first increased to 20°C to 40°C at the third heating rate for hydrothermal treatment for 0.5h to 3h, and then the temperature is increased to 40°C to 60°C at the fourth heating rate for continued treatment for 1h to 3h; preferably, the temperature is first increased to 30°C to 40°C at the third heating rate for hydrothermal treatment for 1h to 2h, and then the temperature is increased to 40°C to 50°C at the fourth heating rate for continued treatment for 1h to 2h; Preferably, the third heating rate and the fourth heating rate are each independently 0.5°C / min to 1.5°C / min, preferably 0.8°C / min to 1.2°C / min; Optionally, in step S3, the conditions of the third hydrothermal treatment include: the hydrothermal temperature is 120°C to 200°C, and the hydrothermal time is 2h to 96h; preferably, the hydrothermal temperature is 150°C to 180°C, and the hydrothermal time is 6h to 72h; Alternatively, the temperature is first increased to 120°C to 160°C for hydrothermal treatment at the fifth heating rate for 1h to 24h, and then the temperature is increased to 160°C to 180°C for continued treatment for 6h to 72h at the sixth heating rate; preferably, the temperature is first increased to 120°C to 140°C for hydrothermal treatment at the fifth heating rate for 1h to 12h, and then the temperature is increased to 165°C to 175°C for continued treatment for 12h to 48h at the sixth heating rate; Preferably, the fifth heating rate and the sixth heating rate are each independently 0.1° C. / min to 3° C. / min, preferably 0.5° C. / min to 1.5° C. / min.
10. The method according to claim 5, characterized in that In step S4, the conditions of the calcination treatment include: a calcination temperature of 350°C to 650°C, and a calcination time of 2h to 10h; preferably, a calcination temperature of 450°C to 600°C, and a calcination time of 4h to 8h; Optionally, the method further comprises: washing and drying the solid product obtained by the solid-liquid separation treatment and then calcining it.
11. Titanium silicon molecular sieve prepared according to the method according to any one of claims 5 to 10.
12. Use of the titanium silicon molecular sieve according to any one of claims 1 to 4 and 11 in catalyzing organic reactions.
13. The use according to claim 12, characterized in that: The catalytic organic matter reaction includes a reaction of preparing propylene oxide by epoxidation of propylene; optionally, the following steps are included: Under epoxidation reaction conditions, propylene, hydrogen peroxide, methanol and a catalyst are contacted to carry out an oxidation reaction; the catalyst comprises the titanium silicon molecular sieve; Preferably, the epoxidation reaction conditions include: a molar ratio of propylene to hydrogen peroxide of 1.0 to 5.0:1, a molar ratio of methanol to hydrogen peroxide of 3 to 10:1, and a weight hourly space velocity of hydrogen peroxide of 0.01 h / min when a fixed bed is used as a reactor. -1 ~3h -1 ; The reaction temperature is 20℃~80℃.
Citation Information
Patent Citations
Method for modifying titanium-silicon zeolite material
CN101850985A
Preparation method for Ti-Si molecular sieve
CN1260241A